Chronotherapy in dipper and nondipper hypertension patients, researching sodium in 24 hours urine and serum urotensin II levels - Kahvecioglu, Fatma Akdag; Ertilav, Muhittin; Varim, Perihan; Varim, Ceyhun (International Journal of Research in Medical Sciences, 2024)
Background: The aim of this research was to study the chronotherapy in patients with differentiated dipper and nondipper hypertension, researching the differences between sodium in 24 hours urine and serum urotensin II. Methods: About 32 nondipper and 29 dipper hypertension patients who have study admission criteria, sodium levels in 24 hours urine, serum urotensin II levels and routine biochemical laboratory tests of were studied. The statistical relationship between the results was analyzed. Results: In the patient group we examined, nondipper patients were found older and predominantly seen in the female patient population. We determined that the dipper patients differed significantly in family history from nondipper patients. Although it is not statistical significance, we observed accordance of treatment who nondipper patients was worse, we have found that serum urotensin II levels can be used at this distinction. Conclusions: It is important to distinguish nondipper and dipper hypertension in terms of the prognosis of hypertension and the efficacy of the treatment. For this reason, we want to underline that nondipper patients are older and predominantly seen in the female patient population. Although left ventricular mass index is important in the course and outcome of hypertension, we determined that is was not useful in distinguishing dipper-nondipper hypertension. We think that serum urotensin II levels will be useful in determining the efficacy of the treatment used, the prognosis of hypertension and the differentiation of nondipper-dipper hypertension.